Emotion-gaze interaction affects time-to-collision estimates, but not preferred interpersonal distance towards looming faces - Yamasaki, Daiki; Nagai, Masayoshi (Frontiers in Psychology, 2024)
Estimating the time until impending collision (time-to-collision, TTC) of approaching or looming individuals and maintaining a comfortable distance from others (interpersonal distance, IPD) are commonly required in daily life and contribute to survival and social goals. Despite accumulating evidence that facial expressions and gaze direction interactively influence face processing, it remains unclear how these facial features affect the spatiotemporal processing of looming faces. We examined whether facial expressions (fearful vs. neutral) and gaze direction (direct vs. averted) interact on the judgments of TTC and IPD for looming faces, based on the shared signal hypothesis that fear signals the existence of threats in the environment when coupled with averted gaze.Experiment 1 demonstrated that TTC estimates were reduced for fearful faces compared to neutral ones only when the concomitant gaze was averted. In Experiment 2, the emotion-gaze interaction was not observed in the IPD regulation, which is arguably sensitive to affective responses to faces.The results suggest that fearful-averted faces modulate the cognitive extrapolation process of looming motion by communicating environmental threats rather than by altering subjective fear or perceived emotional intensity of faces. The TTC-specific effect may reflect an enhanced defensive response to unseen threats implied by looming fearful-averted faces. Our findings provide insight into how the visual system processes facial features to ensure bodily safety and comfortable interpersonal communication in dynamic environments.